Effect of Liuzijue on pulmonary rehabilitation in patients with chronic obstructive pulmonary disease: study protocol for a multicenter, non-randomized, prospective study - Jiaming Hu; Rundi Gao; Yiting Wang; Yan Li; Yaqin Wang; Zhen Wang; Junchao Yang (BMC, 2022)
Abstract Background Traditional Chinese exercise as a new pulmonary rehabilitation technique has been increasingly used and achieved good results in pulmonary rehabilitation of chronic obstructive pulmonary disease (COPD). The aim of this study is to investigate the protective effects of Liuzijue on exercise tolerance, lung function, and quality of life in patients with COPD. Methods This study is a multicenter, non-randomized, prospective study. Patients will be divided into a control group (CG) and a Liuzijue group (LG) based on their willingness to learn Liuzijue. None of the outcome assessors will know the grouping of patients. Participants in this study will be collected from stable COPD patients who are outpatients or inpatients in 3 centers in China since September 2021. Patients will meet the diagnostic criteria for GOLD stage I-II COPD (FEV1% ≥ 0.5 and FEV1/FVC < 0.7) and be aged 40 years or older. Patients voluntarily will take part in the clinical study and sign an informed consent form. All participants will follow their existing medication. For LG patients, Liuzijue training has been added. Patients will practice Liuzijue for more than 30 minutes a day, more than 5 days a week, and adhere to the training for 3 months. Outcome indicators are 6-minute walk test (6MWT), lung function (FEV1%, FEV1/FVC, MMEF, PEF), modified British Medical Research Council (mMRC) score, COPD assessment test score (CAT), acute exacerbations and changes in drug treatment. Discussion This study quantified the effect of Liuzijue on the pulmonary rehabilitation of COPD patients in the stable phase of the disease, and provided a basis for the use of Liuzijue in COPD patients. Trial registration Chinese clinical trial registry, ChiCTR2100048945. Date: 2021-07-19. http://www.chictr.org.cn/showproj.aspx?proj=129094